Interventions to improve treatment, retention and survival outcomes for adolescents with perinatal HIV-1 transitioning to adult care: moving on up. Issue 5 (September 2016) - Judd, Ali; Sohn, Annette H.; Collins, Intira J.
Abstract : Purpose of review: There is an increasing number of deaths among adult survivors of perinatal HIV. Multiple and complex factors drive this mortality, including problems with retention in care and adherence during adolescence, coupled with the critical period of transition from paediatric to adult care, increasing their risk of treatment failure and severe immunosuppression. We reviewed studies that evaluated the impact of service delivery interventions to improve the health of perinatally infected adolescents living with HIV (P-ALHIV) to gain insight into what might help them survive the vulnerable period of adolescence. Recent findings: Youth-focused health services and individual-level interventions may improve P-ALHIV adherence and retention in care. However, there have been few studies, many with small sample sizes and with short durations of follow-up that end before the transition period. Studies from other childhood-onset chronic diseases are similarly limited. Summary: Further studies are urgently needed to identify optimal intervention strategies to reduce mortality and poor outcomes as the adolescent population expands and ages into adult care. Until we have a more robust evidence base, programmes can develop transition plans based on best practice recommendations to optimize the health and longevity of ALHIV in adulthood.